Berm breakwater structures: Features of berm breakwaters and practical experience - Juhl, J. (author); Jensen, O.J. (author) (Imperial College, 1995)
This paper describes the features of benn breakwaters including advantages and drawbacks in comparison to traditional rubble mound structures. A review of selected practical experience with eight berm breakwaters is described in terms of typical cross-sections and key parameters (two examples from Norway. Iceland and USA, and one from Faroe Islands and Australia). In three of the cases described. prototype measurements of the profile development of the berm are available, 'and for two of these a comparison with model tests is shown. The paper includes discussions and examples of required quality assurance programmes for construction of berm breakwaters. Berm Breakwaters